PERLINDUNGAN PASAR TRADISIONAL DARI DAMPAK PERKEMBANGAN PASAR MODERN DALAM PERSPEKTIF PERLINDUNGAN HUKUM DARI PERSAINGAN USAHA TIDAK SEHAT - , Tavip Purnomo Hadi ([Yogyakarta] : Universitas Gadjah Mada, 2012)
The research objective of this thesis is to describe the role of government in providing protection in a democracy for the sake of economic prosperity and welfare, protect the traditional markets of the modern market share dominance of monopolistic practices and unfair competition, to explore the rules that already exist to optimize the arrangement for controlling the construction of modern markets so as not to shift the traditional market presence and local governments to identify compliance with existing regulations on the arrangement of modern and traditional markets. The research method used in this study is a normative legal research methods with qualitative approaches. Qualitative research methods have 4 (four) steps should be taken that the quality/ qualification data obtained from the results of the study, arranged in a systematic study, the deduction is done using an inductive method that concludes a case with a set of theories, doctrines and laws legislation leads to general conclusions and answer the problems. Data collection techniques used in this research is literature study and determination of the location of this research used purposive sampling method for sampling is based on specific goals. The Study concluded, the protection of the Government in enforcing the Economic Democracy: The Government has issued Law No. 5/199 on the Prohibition of Monopolistic Practices and Unfair Business Competition, President Regulation No. 112/2007 and Minister of Trade Regulation No. 53/2008 about Structuring and Fostering Traditional Markets of the Modern Market dominance set forth in Article 50 of Law No.5/1999 letters h and i the article exemption for Small Businesses and Cooperative. To control the growth of Modern Markets, the Government has issued President Regulation No. 112/2007 and Minister of Trade Regulation No.53/2008 on Guidelines for Planning and Development of Traditional Markets, Shopping Center and Modern Stores. The majority of Local Government is not ready to set strict Modern Markets in the region, which is evidenced by the absence of rules derived from National Regulation in the area. Local Governments already have Local Rules as a rule derived for implementation of Presidential Regulation No.112/2007 and Trade Minister Regulation No.53/2008 is the Provincial Government of East Java, Surabaya City Government, City Government Bandung and Denpasar.